DPP-4 inhibitory activity and myocardial salvaging effects of Commiphora mukul in experimental diabetes - Borde, Manjusha K.; Mohanty, Ipseeta Ray; Maheshwari, Ujwala; Suman, Rajesh Kumar; Deshmukh, Y. A. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Commiphora mukul (Burseraceae) is commonly known as Guggul in Ayurveda. Several studies have reported antidiabetic activity of Commiphora mukul but there are no studies to explore the DPP-4 inhibitory activity and myocardial salvaging effects of Commiphora mukul in setting of diabetes mellitus. The present study was designed to evaluate the cardioprotective efficacy as well as safety of the medicinal plant Commiphora mukul (Guggul) in the experimental model of myocardial infarction co-existing with diabetes. Methods: Diabetes was induced with single dose of streptozotocin (STZ): 45mg/kg ip and myocardial infarction was produced by administering isoproterenol (ISP): (85mg/kg, sc) to rats 24 and 48 h prior to scarification (5th week). After the confirmation of diabetes on 7th day (glucose>200mg/dl), vildagliptin (10 mg/kg) and Commiphora mukul (200 mg/kg) were administered orally from 1st to 5th week (4 weeks). At the end of experimental period, normal control, diabetic-isoproterenol control, vildagliptin and Commiphora mukul group rats were sacrificed for further biochemical investigations as well as histopathological evaluation. Results: Commiphora mukul treatment demonstrated significant antidiabetic as well as myocardial salvaging effects as indicated by restoration of blood glucose, HbA1c and CPK-MB serum DPP-4, hs-CRP levels as compared to diabetic ISP control group. In addition, Commiphora mukul showed significant cardioprotection as indicated by positive correlation between cardiac marker CPK-MB and serum DPP-4. The histopathological assessment of heart, pancreas and biochemical indices of injury confirmed the cardioprotective effects of Commiphora mukul. In addition, Commiphora mukul was found to be safe to the liver and kidney. Conclusions: The natural DPP-4 inhibitor Commiphora mukul demonstrated significant cardioprotective effects in experimental model of myocardial infarction co-existing with diabetes.